Microplastics in Human Thoracic Tissues: Increased Burden in Patients with Lung Malignancy - Ilias E. Dimeas; George E. Zakynthinos; Christos Salmas; Ioannis Diamantis; Maria Giannaki; Charalampos Varsamas; Achilleas Sarris; Angeliki Miziou; Paraskevi Kirgou; Sotirios I. Sinis; Kathryn Duvall; Stavros P. Anastopoulos; et al. (Journal of Clinical Medicine, 2026)
Background: Human respiratory exposure to microplastics (MPs) has recently been demonstrated, but their distribution within thoracic tissues and association with lung malignancy remain poorly characterised. We investigated the presence, burden, morphology, and spectroscopic characteristics of MPs in thoracic tissue specimens and their relationship with lung malignancy. Methods: In this prospective observational study, 50 adults undergoing diagnostic thoracic surgical procedures for suspected lung malignancy were enrolled. Lung, pleural, and mediastinal lymph node specimens underwent contamination-controlled processing, microscopy, and representative particle analysis by confocal micro-Raman spectroscopy. Associations between MPs and clinicopathological variables were analysed. Results: Sixty-two morphologically identified microplastic particles were detected in 50 specimens, with MPs detected in 32 patients (64%). Fragments accounted for 97% of particles, with a median burden of one particle per specimen (IQR, 2). MP detection was significantly more frequent in patients with primary lung malignancy than in patients without primary lung malignancy, including those with metastatic malignancy and benign disease (81.8% vs. 50.0%, p = 0.020), who also exhibited a higher tissue MP burden (p = 0.024). Primary lung malignancy remained independently associated with MP detection after adjustment for age and smoking exposure (OR 4.09, 95% CI 1.06–15.79; p = 0.041). Particle morphology varied by biopsy site, with significantly smaller particles identified in mediastinal lymph nodes (p = 0.006). Synthetic anthropogenic spectral signatures were identified in 71% of particles. Conclusions: MPs are frequently present in human thoracic tissues and are associated with primary lung malignancy. Compartment-specific particle characteristics suggest distinct patterns of respiratory MP deposition and retention, supporting multicentre mechanistic studies.